Transnationalism in the Field of Art in Greece: The Case of the International Exhibition of Athens in 1903 - Papandreopoulou, Katia (Historein, 2023)
The study examines the artistic production of the early twentieth century in Greece in the light of the transnational approach. The static myths prevalent in the historiography of Greek art in the twentieth century are revised through the study of the circulation of artists, sources, exchanges, connections, or resistances, as well as local or international participation in exhibitions regarding this period. The study of the case of the International Exhibition of Athens, including its curation and the artists who entered it, that took place in the Zappeion Megaron in 1903, proves that the Greek artistic production of the period was not marginal and belated. On the contrary, Athens, a periphery with particular geographical and cultural dynamics, interacted with the Mediterranean and the Balkans, highlighted its own networks and routes, thus managing to function as a crossroads of innovations and traditions of the wider region at the beginning of the twentieth century.